2016
DOI: 10.1155/2016/7170610
|View full text |Cite
|
Sign up to set email alerts
|

Refreshing Sleep and Sleep Continuity Determine Perceived Sleep Quality

Abstract: Sleep quality is a construct often measured, employed as an outcome criterion for therapeutic success, but never defined. In two studies we examined appraised good and poor sleep quality in three groups: a control group, individuals with obstructive sleep apnea, and those with insomnia disorder. In Study 1 we used qualitative methodology to examine good and poor sleep quality in 121 individuals. In Study 2 we examined sleep quality in 171 individuals who had not participated in Study 1 and evaluated correlates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 20 publications
2
29
0
1
Order By: Relevance
“…Sleep continuity (infrequent nocturnal awakenings) is a hallmark of good sleep [34]. Aging adults [35, 36] and diabetes patients [35] are at particular risk for frequent nocturnal awakenings.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep continuity (infrequent nocturnal awakenings) is a hallmark of good sleep [34]. Aging adults [35, 36] and diabetes patients [35] are at particular risk for frequent nocturnal awakenings.…”
Section: Discussionmentioning
confidence: 99%
“…A similar small percentage continued to experience nonrefreshing sleep, and slightly elevated anxiety and depression. Correlational data indicated that nonrefreshing sleep, an important marker of sleep quality [ 25 ], was significantly related to virtually all nocturnal sleep variables. This pattern of findings may reflect a preexisting tendency to sleep difficulty, anxiety, and impaired mood in a small percentage of mothers that does not respond to what is usually considered as the improved conditions of the 6-month postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…I sleep about ____ hours per night.”). Sleep quality was assessed with a non-validated question by asking “When you wake up from sleeping, how refreshed do you feel?” (0) “Never refreshed,” (1) “A little or somewhat refreshed,” (2) “Moderately refreshed,” (3) “Mostly refreshed,” (4) “Very refreshed,” because refreshed sleep is a key indicator of high-quality sleep ( Libman et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%